y = cos 5 x + 5 cos 3 x + 1 0 cos x cos 6 x + 6 cos 4 x + 1 5 cos 2 x + 1 0
If y is defined as above, what is d x d y ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
In the last term it will be 10(2cos²x) The rest is just perfect Good one!
y ⟹ y ⟹ d x d y = cos 5 x + 5 cos 3 x + 1 0 cos x cos 6 x + 6 cos 4 x + 1 5 cos 2 x + 1 0 = cos 5 x + 5 cos 3 x + 1 0 cos x cos 6 x + 5 cos 4 x + 1 0 cos 2 x + cos 4 x + 5 cos 2 x + 1 0 = cos x ( cos 4 x + 5 cos 2 x + 1 0 ) − sin x ( sin 4 x + 5 sin 2 x ) cos 2 x ( cos 4 x + 5 cos 2 x + 1 0 ) − sin 2 x ( sin 4 x + 5 sin 2 x ) + cos 4 x + 5 cos 2 x + 1 0 = cos x ( cos 4 x + 5 cos 2 x + 1 0 ) − sin x ( sin 4 x + 5 sin 2 x ) ( 2 cos 2 x − 1 ) ( cos 4 x + 5 cos 2 x + 1 0 ) − 2 sin x cos x ( sin 4 x + 5 sin 2 x ) + cos 4 x + 5 cos 2 x + 1 0 = cos x ( cos 4 x + 5 cos 2 x + 1 0 ) − sin x ( sin 4 x + 5 sin 2 x ) 2 cos x [ cos x ( cos 4 x + 5 cos 2 x + 1 0 ) − sin x ( sin 4 x + 5 sin 2 x ) ] = 2 cos x = − 2 sin x
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Sum to Product Trigonometric Identities
Simplify numerator as follows:
( cos 6 x + cos 4 x ) + 5 ( cos 4 x + cos 2 x ) + 1 0 ( cos 2 x + 1 )
Use cos 2 A + cos 2 B = 2 cos ( A + B ) cos ( A − B ) and cos 2 x + 1 = 2 cos 2 x so that numerator is:
2 cos x cos 5 x + 5 ( 2 cos x cos 3 x ) + 1 0 ( 2 cos x ⋅ cos x )
We see this is exactly 2 cos x times the denominator. Hence we get:
y = 2 cos x
∴ d x d y = − 2 sin x